Comparative Analysis of Household Debt Levels and Structures in European Countries: Trends and Implications - Grzywińska-Rąpca, Małgorzata; Zawadzka, Agnieszka (Analiza porównawcza poziomu i struktury zadłużenia gospodarstw domowych w krajach europejskich: trendy i implikacje, 2025)
Aim: The aim of the article was to analyse the level and structure of household indebtedness in selected European countries over two periods: 2018–2019 and 2020–2022. The research focused on two key objectives: (1) a comparative analysis of the forms of indebtedness among households in different European countries, and (2) a comparative analysis of the euro area and non-euro area EU Member States with respect to the level and structure of household debt. Methodology: The study is based on secondary data from Eurostat concerning the financial resources and debt levels of European households. The analysis covered two distinct time periods (2018–2019 and 2020–2022) and compared the prevalence and structure of different debt instruments. The research included descriptive and comparative methods, examining household behaviour in euro area and non-euro area countries. Results: The analysis showed that there were no statistically significant differences between euro area and non-euro area households in terms of asset and debt categories. In the euro area, households more frequently used short-term and long-term loans, while they were less likely to invest in quoted shares and bonds. In non-euro area countries, short-term loans dominated, suggesting a stronger tendency to use quick access financing tools. Debt securities and long-term loans were less prevalent in these countries. Implications and recommendations: The findings suggest that household debt preferences were relatively stable across Europe, with minor regional differences. Policymakers should consider these patterns when designing financial literacy programmes and credit regulations. Future research could focus on the behavioural factors influencing household debt decisions and investigate the impact of macroeconomic changes on these trends. Originality/value: This study contributes to the literature by offering a comparative perspective on household indebtedness in euro area and non-euro area countries, using up-to-date Eurostat data across two relevant time frames. It provides insights into the structure of household liabilities and the regional differences in debt preferences.
Econometrics = Ekonometria, 2025, Vol. 29, No. 2, s. 19-37
Keywords: household debt; euro area; financial structure; comparative analysis; consumer credit; zadłużenie gospodarstw domowych; strefa euro; struktura finansowa; analiza porównawcza; kredy konsumencki